Penerapan Model Pembelajaran Contextual Teaching and Learning pada Sekolah Menengah Kejuruan - Ilham Juliwardi; Ganefri Ganefri (VOCATECH: Vocational Education and Technology Journal, 2021)
AbstractThis research is motivated by the low percentage completeness results of class X student TITL2 in SMK N 1 Pariaman on subjects (MRL) to the basic competence to analyze a series of alternating current (AC) according to ohms law, which is still a lot of students have not reached KKM is 75. One of the factors that influence student learning outcomes are poor learning model. To view the learning outcome using the learning model, a research by applying the learning model Contextual Teaching and Learning. Learning Model CTLis a learning model that has components in it that can emphasize the students more active and participate. The purpose of this study was to determine the improvement of student learning outcomes in subjects MRL by applying the Learning Model of CTLclass X TITL 2 in SMK 1 Pariaman. This research is a quasi experiment with pretest-posttest design one group. The instrument used was a pre-test and post-test. Such an instrument before used first tested the validity of the obtained 25 about the pre-test and 26 about the post-test are valid, research results overall as calculated seen an increase learning outcomes with an average g = 0,462 category was the student learning outcomes before and after using model Contextual teaching and learning.Keywords:Improvement; Contextual Teaching and Learning; learning outcomes__________________________AbstrakPenelitian ini dilatarbelakangi oleh rendahnya persentase hasil ketuntasan siswa kelas X TITL2 di SMK N 1 Pariaman pada mata pelajaran (MRL) terhadap kompetensi dasar menganalisis rangkaian arus bolak-balik (AC) menurut hukum ohm yang masih banyak siswa yang belum mencapai KKM adalah 75. salah satu faktor yang mempengaruhi hasil belajar siswa adalah model pembelajaran yang kurang baik. Untuk melihat hasil belajar menggunakan model pembelajaran, dilakukan penelitian dengan menerapkan model pembelajaran Contextual Teaching and Learning. Model Pembelajaran CTLmerupakan model pembelajaran yang memiliki komponen-komponen di dalamnya yang dapat menekankan siswa lebih aktif dan berpartisipasi. Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar siswa pada mata pelajaran MRL dengan menerapkan Model Pembelajaran CTL kelas X TITL 2 di SMKN 1 Pariaman. Penelitian ini merupakan penelitian eksperimen semu dengan desain pretest-posttest one group. Instrumen yang digunakan adalah pre-test dan post-test. Instrumen tersebut sebelum digunakan terlebih dahulu diuji validitasnya diperoleh 25 tentang pre-test dan 26 tentang post-test yang valid, hasil penelitian secara keseluruhan yang dihitung terlihat adanya peningkatan hasil belajar dengan rata-rata g = 0,462 kategori sedang siswa hasil belajar sebelum dan sesudah menggunakan model Contextual teaching and learning.Kata Kunci:Peningkatan; Contextual Teaching and Learning; Hasil Belajar__________________________